Multiple Bilateral Ovarian Mature Cystic Teratomas with Ovarian Torsion: A Case Report - Fayez, Iman (Oman Med J, 2018)
Ovarian tumors are a common form of neoplasm in women. Mature cystic teratoma is the most common type, with a bilateral incidence of 8–15%. However, few cases are reported as bilateral and multiple. A rare case of bilateral multiple dermoid cysts in a 19-year-old female patient presented with abdominal pain of one-day duration. Her medical history was unremarkable. Ultrasonography showed multiple bilateral ovarian cystic masses. The patient underwent laparotomy. The masses were excised while preserving the remaining ovarian tissue. Histopathology confirmed the diagnosis of multiple mature cystic teratomas with no presence of malignant tissue.